1991
DOI: 10.1111/j.1151-2916.1991.tb06782.x
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous Processing of Mullite‐Containing Green Sheets

Abstract: An aqueous-based slurry for tape-casting mullite sheets was studied that is suitable for electronic packaging. A latex binder was used to attain the necessary organic content in the tape while maintaining a low slurry viscosity. The colloidal stability of these complex slurries was characterized by electrokinetic sonic amplitude (ESA) measurements and sedimentation experiments. Control of dispersion stability required the addition of a polyelectrolyte. Suitability of the aqueous-based tapes for multilayer pack… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(21 citation statements)
references
References 3 publications
1
20
0
Order By: Relevance
“…21 Similarly, Ushifusa and Cima determined the isoelectric point of B-60A at about pH 2 in absence of any electrolyte. 14 Fig . 3 shows the viscosity of the hydroxypropyl methylcellulose solution as a function of concentration.…”
Section: Solution Propertiesmentioning
confidence: 99%
See 2 more Smart Citations
“…21 Similarly, Ushifusa and Cima determined the isoelectric point of B-60A at about pH 2 in absence of any electrolyte. 14 Fig . 3 shows the viscosity of the hydroxypropyl methylcellulose solution as a function of concentration.…”
Section: Solution Propertiesmentioning
confidence: 99%
“…13 Similarly, Ushifusa and Cima developed latex-based slurry for tape casting of mulliteglass composites suitable for electronic packaging. 14 Thermal analysis and microstructural characterization of PMN films prepared by aqueous tape casting in the presence of acrylicbased binder was studied previously by Ş akar-Deliormanlı et al 17 The aim of the current work is to prepare aqueous-based PMN slurries to use in tape casting process and investigate the final properties of the PMN films. The films were manufactured using a doctor blade having the gap height of 30-500 m. The results of the study showed that it is possible to prepare high quality PMN films based on aqueous formulations.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…A well known example of a solvent-soluble binder is polyvinyl butyral (PVB), water-soluble binders are poly vinyl alcohol (PVA), latexes or methyl cellulose (MC). [10][11][12][13][14] Few examples are known were a natural compound is used in the tape casting process. [15] In this paper we discuss the fabrication of mullite substrates by water-based tape casting for the development of polycrystalline solar cells, using a commercial acryl latex binder.…”
mentioning
confidence: 99%
“…The technique uses a colloidal suspension containing a binder, that is either solvent or water soluble. [10,11] Although water-based tape casting would be preferred from an environmental point of view, solvent based tape cast processes are considered to be more robust and easier to control.…”
mentioning
confidence: 99%